Surface gravity and effective temperature of the K5 subdwarf G 224-58 A and Arcturus from the fits to Ti and MgH lines - Kushniruk, I.O.; Pavlenko, Ya.V.; Gálvez-Ortiz, M.C.; Zhang, Z.H. (Advances in Astronomy and Space Physics, 2016)
We discuss here the results obtained in the determination of effective temperatures and metallicities of late-type stars. We provide the abundances of MgH, Ti ı and Ti װ, with a list of selected lines, for the red giant of Arcturus and the metal-poor K subdwarf G 224-58 A. The Sun was used as a template star. After computing synthetic spectra for model atmospheres with different Teff and log g values, we used minimization procedures to determine the best fits to the observed features. The determination of Ti abundances was carried out in the framework of a self-consistent approach developed by Pavlenko et al. (2012). In the case of MgH we used similar minimization procedure. We present here the combination of two different approaches based on the fits performed to Ti and MgH, respectively. The resulting effective temperatures are Tₑff = 4300 K for Arcturus and Tₑff = 4600 K for G 224-58 A, where both solutions are degenerated with log g.